2001
DOI: 10.1063/1.1354632
|View full text |Cite
|
Sign up to set email alerts
|

Elastic properties of nanocrystalline zirconium–silicon–boron thin films

Abstract: Thin amorphous films of ZrB3 grown on Si(111) substrates by chemical-vapor deposition are, upon annealing at 960 °C, transformed to films composed of nanocrystallites (6–10 nm extent) with a nominal composition of Zr0.9Si0.3B3. The independent elastic constants of the layers are determined from the dispersion of the surface and pseudo-Sezawa acoustic excitations and reveal large enhancements in the C11 and C44 constants accompanying the conversion of ZrB3 to the nanocrystalline phase. Since the transverse soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In order to monitor closely the evolution of growth in real time, the ZrB 2 growth rate in the LEEM was deliberately set to less than half of the growth rate in a GSMBE chamber reported earlier [2]. In previous studies, it was found that high growth rates would invariably lead to growth of amorphous ZrB 2 films [8,9]. The growth process was followed by the LEED patterns and LEEM images taken in real time.…”
Section: Methodsmentioning
confidence: 99%
“…In order to monitor closely the evolution of growth in real time, the ZrB 2 growth rate in the LEEM was deliberately set to less than half of the growth rate in a GSMBE chamber reported earlier [2]. In previous studies, it was found that high growth rates would invariably lead to growth of amorphous ZrB 2 films [8,9]. The growth process was followed by the LEED patterns and LEEM images taken in real time.…”
Section: Methodsmentioning
confidence: 99%
“…Brillouin scattering is a sensitive investigative tool for studying the elastic properties of both free standing and supported films by detecting the surface and/or bulk acoustic modes. A change in, for instance, the sample crystallographic structure, physical hardness and elastic energy, is manifested as a frequency shift of acoustic modes or appearance of new modes, travelling on the surface or within the films [9][10][11][12][13]. This paper reports on results of Brillouin scattering from pSi films that were separately passivated with 1-decene, decyl aldehyde, undecylenic acid and ethyl undecylenate.…”
Section: Introductionmentioning
confidence: 99%